Benefits of scientific tourism in a mega-diverse forest landscape: Case of the Kichwa community in San José De Payamino, Ecuadorian Amazon - Izurieta, Gabriela (2020)
This document analyses the benefits of scientifictourism (ScT) at a community level from a social,economic, environmental and cultural points of view. Theresearch was carried out at the Timburi Cocha BiologicalStation (TCBS) within the Kichwa community of San Joséde Payamino, located in the buffer zone of the SumacoNapo Galeras National Park (SNG-NP) in the SumacoBiosphere Reserve (SBR) and is part of one of the world’sAndean-Amazonian biodiversity hotspots. We employedthe methodology of scientific observation, householdsurvey and interviewing community leaders and leaders ofthe two main academic entities involved with the TCBS.The results show that the activities of ScT has contributedto the San José de Payamino community with an annualaverage ranging from 3474 to 5000 USD in the last eightyears. In addition to other economic, social, environmentaland cultural benefits as a result of the involvement ofcommunity members in the different activities carriedout by the EBTC. The “Community Leaders” revealed“high” weights on issues related to: a) respect for ancestralknowledge; b) respect and conservation of NRNs; c)empowerment or respect for cultural identity; d) respect forthe Kichwa language and; d) participation of communitymembers in the activities carried out in the EBTC, while; e)mutual learning obtained a “medium” weighting. Finally,the document presents recommendations to improve thebenefits of the TCi activities carried out in the EBTC, aswell as to contribute to the sustainable development andconservation of the community’s natural resources.